Développement de marqueurs moléculaires liés à la résistance à la mortalité estivale chez l'huître creuse Crassostrea gigas - Approche QTL - Sauvage, Christopher (Université de La Rochelle, 2008)
The Pacific oyster Crassostrea gigas is the most cultivated marine species in the world (4.2 million tonnes for a turnover of 3.5 billion US dollars according to the FAO 2005). Flat oyster culture is one of the components of the French economic activity. However, for more than 15 years, farms have had to face some summer mortality episodes (30 %-60 %), that could jeopardize European mollusc culture competitivity. More than the economical importance of C. gigas, which justifies a great research effort, oysters constitute a study model of the complex physiological and genetic basis (i.e. growth, reproduction, and survival) strongly correlated to the oyster's response to different environmental conditions. One of the considered solutions is the selection of individuals which are more resistant to mortality. Considering the constraints linked to the setting up of such selection schemes, the development of genetic markers, enabling a marker aided selection, seems to be an interesting research direction to follow but it also aims at better understand summer mortality in the cupped oyster through the study of the genetic architecture of this phenomenon. Moreover, knowledge of the genome of the cupped oyster is currently blooming (Hedgecock, Gaffney et al. 2005). It appears as particularly polymorphous and has a large number of recessive deleterious genes, responsible for some important segregation distortions (Launey and Hedgecock, 2001). A map of the bonding, based on a hundred microsatellite markers, has been published recently (Hubert and Hedgecock, 2004).Carried out in the framework of the European project "Aquafirst" (FP6), this thesis aims to develop a cartography enabling the detection of the genotype/phenotype relationship based on a QTL (Quantitative Trait Locus) approach. The considered phenotype trait is the summer mortality in the cupped oyster Crassostrea gigas. In this way, a range of new molecular markers of SNP (Single Nucleotide Polymorphism) type have been developed in order to draw a genetic map ...